2013
DOI: 10.1177/0892705713495431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental degradation and mechanical properties of polyamide 6-grafted carbon fiber/poly(3-hydroxybutyrate-co- 3-hydroxyvalerate) composites

Abstract: The measured mechanical properties of carbon fiber/polyamide 6 (CF/PA6) laminates decreased with exposure time at 60 C and 100% relative humidity. Both the bending stiffness and the strength degraded to a level of about 65%, whereas interlaminar shear strength (ILSS) dropped to about 87% of the property values of the unexposed material. The bending stiffness and strength at À45 C are about 87% of the properties at room temperature, whereas at 115 C, the stiffness drops to 75% and the strength drops to 60% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…[4,5] Briscoe et al, for example, found that the damage brought about by torsional contact was more detrimental than those reduced by the rolling or rotating contacts. [6,7] However, the torsional wear behaviour of TiO 2 /P-Methoxymethamphetamine(PMMA)/ Ti 6 Al 4 V alloy and TiO 2 /PMMA/Al 2 O 3 has not been clearly discussed. In this research, a new testing method is used to reveal the damage characteristics of TiO 2 /PMMA/Ti 6 Al 4 V alloy and TiO 2 /PMMA/Al 2 O 3 caused by torsional fretting wear.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Briscoe et al, for example, found that the damage brought about by torsional contact was more detrimental than those reduced by the rolling or rotating contacts. [6,7] However, the torsional wear behaviour of TiO 2 /P-Methoxymethamphetamine(PMMA)/ Ti 6 Al 4 V alloy and TiO 2 /PMMA/Al 2 O 3 has not been clearly discussed. In this research, a new testing method is used to reveal the damage characteristics of TiO 2 /PMMA/Ti 6 Al 4 V alloy and TiO 2 /PMMA/Al 2 O 3 caused by torsional fretting wear.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fibres (cellulose fibres (CFs)), due to their unique mechanical properties, have been widely used as reinforcements in polymer composites. 13 To obtain CF-reinforced polymers (CFs/polymers) with good mechanical properties, several parameters such as orientation of CF in the matrix, dispersibility of CF in the matrix, diameter of CF, matrix stiffness and the interfacial shear strength between the CF and the matrix should be considered.…”
Section: Introductionmentioning
confidence: 99%